Nanocellulose from rice husk following alkaline treatment to remove silica - Ludueña, Leandro Nicolas (2011)
The present work deals with the use of multiple-step procedures to obtain valuable sub-products, including nanocellulose, from rice husk. Each sub-product was characterized after every step by analyzing the chemical composition (mainly based on thermogravimetric analysis, Fourier transformed infrared spectra, and X-ray diffraction) and morphology (using visual observations and scanning electron microscopy). The results clearly showed that the selected procedure gave the possibility to separate silica in the first step and then to purify the resultant material, leading to nanocellulose production. All acquired sub-products can be used as additives and fillers in a very wide range of applications. The obtained results will be useful both from technological and academic points of view, mainly for people working in the field of biocomposites. The final material could give added value to a raw biomass material source such as rice husk.